Analysis of the Determinants of Eldery Proverty in Indonesia in 2022 - Napitupulu, Normalina; Hasudungan, Raju; Amanda, Dila; Sylvia, Bebby (Journal of Research in Mathematics Trends and Technology, 2022)
Indonesia is entering a period of demographic bonus with the lowest projected dependency ratio in 2030. This bonus is expected to accelerate the development of various sectors. However, the increase in the number of elderly people, which reached 9.78% in 2020, signifies the potential of the ageing population era. Special handling is needed to avoid negative impacts on development and the risk of elderly poverty. This study uses a survey of 300 elderly people and binary logistic regression analysis to evaluate the factors that influence elderly poverty. The results showed that education, working status, area of residence, marital status, and social security had a significant effect, while functional impairment did not. Recommendations include improving access to education and equitable distribution of elderly social security programmes across Indonesia.